Effects of Root Exudates on Specific Diazotroph-Rice Genotype Association - Naher, Umme Aminun (2009)
Diazotrophs are known to utilize root exudate carbon compounds, form natural associations with rice plants and subsequently fix nitrogen. The specific association can be influenced by the bacterial strains and rice genotypes. A series of experiments were conducted in laboratory and glasshouse conditions with the following objectives; (i) to isolate and characterize the indigenous diazotrophs, (ii) to determine the root exudate sugars and amino acids of different rice genotypes (iii) to determine the utilization of root exudates sugars by the diazotrophs (Rhizobium sp. and Corynebacterium sp.) during colonization and (iv) to determine the effects of specific sugars on plant-diazotrophs associations, biological nitrogen fixation and growth of different rice genotypes. The diazotrophs were isolated from Tanjong Karang rice irrigation project area using N-free semi-solid media and the nitrogenase enzyme activity was determined by Acetylene Reduction Assay (ARA) technique. The isolated diazotrophs were identified using Biolog Identification method. Root exudates sugars and amino acids of the three rice genotypes (Mahsuri, Mayang Segumpal and MR219) were determined using high performance liquid chromatography (HPLC). The root (rhizosphere and endophytic) colonization were visually observed by using Scanning Electron Microscope (SEM) and Transmission Electron Microscope (TEM). The diazotroph–plant association and biological nitrogen fixation (BNF) was estimated using 15N dilution technique in glasshouse condition. Results showed that the indigenous diazotrophic populations were significantly (P<0.01) influenced by soil types, plant age and rice varieties. Bacterial populations were significantly higher in soil (1.8-2.2 x 106 cfu g-1soil) and rhizosphere (1.4-4.2 x 107 cfu g-1 root) of rice grown in Organic Clay & Muck, Bakau, Sedu and Serong soil series. Molecular analysis indicated a diverse group of diazotrophic strains were present in the different soil types. Ten of the strains were identified by the Biolog Identification method as Rhizobium, Burkholderia and Corynebacterium spp.. Biochemical tests of 19 isolates showed that these strains were positive for N2 fixation, capable of degrading cellulose and able to produc high amounts of indoleacetic acid (IAA) which ranged from 15 to 69 mg L-1. The diazotrophs exhibited differences in the specific growth rate, generation time, and utilized mono and disaccharide sugars as sole energy sources. A total of seven sugars and 16 amino acids were determined from rice root exudates. The concentration of root exudate sugars, amino acids and their release patterns differed significantly among rice genotypes. Mahsuri released the highest root exudate sugars (25.73%) followed by MR219 (23.14%) and Mayang Segumpal (20.85%). Inoculated plants produced different amounts of sugars and amino acids compared to non-inoculated plants. Mahsuri inoculated with Corynebacterium sp. (Sb26) released the highest amount of fructose and arabinose, while Mayang Segumpal inoculated with Rhizobium sp. (Sb16) produced the highest amount of sucrose in the root exudate. All rice genotypes produced significantly higher amounts of glycine and isoleucine in root exudates as compared to other amino acids. In general, plants inoculated with Sb16 produced higher amounts of total sugars and amino acids in their root exudates compared to those inoculated with Sb26. A significant relationship was observed between diazotrophic populations and utilization of root exudates sugars and amino acids in the rice genotypes. The Sb16 strain utilized higher amounts of sugars and stimulating higher rhizosphere population compared to Sb26 strain. The diazotrophs were able to colonize and proliferate endophytically in the rice roots. SEM micrographs showed the occurrence of bacterial colonization on surfaces of primary and lateral roots, root hair zone, lateral root junction, in crevices and root tips. TEM view of roots revealed the presence of diazotroph in the intercellular spaces of cortical parenchyma, within epidermis, inner cortex, and near vascular tissue. The results of invitro and glasshouse study using 15N dilution studies showed that Mayang Segumpal inoculated with Sb16 and applied with galactose significantly increased plant-N content and fixed 42 % of atmospheric N (Ndfa). This association increased 147-245 % plant biomass compared to non-inoculated control and 8-52 % over 60 kg ha-1 N-fertilizer application.The study proved that diazotroph inoculation enhanced root exudate sugar production and provides specific sugars for specific diazotroph-rice plant association. Application of galactose and arabinose as external carbon source enhanced the growth and N2 fixation activity of the Rhizobium sp. (Sb16) and Corynebacterium sp. (Sb26), respectively. The association of Mayang Segumpal with Sb16 and MR219 rice with Sb26 significantly improved nitrogen fixation and subsequently plant growth.